(untitled) (Bangladesh Journal of Zoology, 2015)
Realizing the importance of giant freshwater prawn, Macrobrachium rosenberbii supply mature brood for extending the culture period for the successful production of marketable size, a study was conducted for development of broods of the species in the winter season by increasing temperature of water using green house concept. For this purpose, two ponds were covered with transparent polyethylene sheet fastened in bamboo frame and two ponds with no such covering. The ponds were equally stocked with prawn @ 5000 indv./ha (female:male::8:1) on 8th December 2009 and reared up to 9th March 2010. Temperature of water of the green house ponds was much higher than that of open ponds. Prawns started to be gravid after stocking in the green house ponds and 45-55% prawn became berried up to 9th March. But no remarkable development of gonad except a very few (2.5%) gravid prawn at the later part of rearing in one of the open pond was observed. Bangladesh J. Zool. 42(2): 153-159, 2014